Promoting and Supporting Breastfeeding in Postpartum Mothers with Cesarean Section - Tharana, Nopparat (Nursing Journal CMU, 2021)
Cesarean section is affecting breastfeeding. Postpartum mothers have shown that incision pain, fatigue from blood loss, postural limitation, which is an obstacle to breastfeeding. As well as delay the initial breastfeeding, affects the production and lactation. Therefore, promoting and supporting breastfeeding for women undergoing cesarean section is critical. This article has the objective in promoting and supporting breastfeeding in postpartum mothers with cesarean section, introducing the current situation of cesarean section, problems of mothers after cesarean that affect breastfeeding, and nurse - midwives should providing knowledge about breastfeeding from pregnancy, childbirth, and postpartum, immediately or early skin-to-skin contact and initial breastfeeding, providing enough water and nutrients, relieve pain while breastfeeding, rooming in, assist to positioning, breast massage and hot compress in 24 – 48 hours after cesarean birth, latching on and suckling every 2 - 3 hours, psychological support, and follow up on breastfeeding after the mother leaves the hospital. To allow mothers after cesarean birth to continue breastfeeding and successful breastfeeding.